توظيف الآيات الكونية القرآنية في بناء وحدات دراسية لتعليم مهارة القراءة : المستوى المتقدم - عثمان، أحمد شيخ محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1998)
The purpose of this study is to examine the Quranic verses relating to natural phenomena and the way these verses are used to teach Arabic to non-native speakers. The study analyzes nature as a whole and the Quranic style of the verses pertinent to it. It collects the vocabulary items found therein, and establishes the principles for the utilisation of these verses in order to design appropriate study modules. Based upon an inductive method of analytical description, the study found that, the Qur' an discusses different natural phenomena in a variety of linguistic styles, such as, metaphors, similes, puns and the like. It also found that there is no unified consensus among scholars on principles by which these verses could be utilized in the teaching of Arabic language to non-Arabs. Consequently the study adopts the well known criteria for selection of vocabulary, content and method. The study shows that utilizing Qur' anic verses on natural phenomena is a fruitful approach to facilitate.teaching Arabic language to non Arabs. The topics covered by these verses in the Quran are varied, and the vocabulary items used on natural phenomena are simple and concrete in a way to fully serve the purpose of teaching Arabic to non-Arabic speaking learners.